Factores de riesgo asociados a infección urinaria recurrente en niñas de 6 -12 años - Sánchez Otiniano, Raquel Elizabeth (2017)
To assess the risk factors associated with recurrent urinary tract infection in girls aged 6-12 years of the Regional Teaching Hospitals of Trujillo and Belén de Trujillo. METHODOLOGY: retrospective analytical study, case and control type. MATERIAL AND METHOD: 182 clinical records (91 cases and 91 controls) of the pediatric service of hospitals were reviewed: Regional Teaching of Trujillo and Belén de Trujillo. The level of association was evaluated with the Odss ratio (OR) and its significance with the Chi square test. RESULTS: Urinary malformations were 19.8% with p = 0.0021 and OR: 7.23 (95% CI: 2.05 - 25.52), vesicoureteral reflux was 6.6% with p = 1, and OR: 1 (95% CI: 0.31- 3.22), bladder dysfunction was 73.6% with p = 0.74 and OR = 1.12 (95% CI: 0.58-2.14), constipation had 31.8% with p = 1 and OR = 1 (95% CI: 0.54 - 1.86) and 1% neurogenic bladder with p = 1 and OR = 1 (95% CI: 0.06 - 16.23). The double ureter was 3.3%, the ureterophexis was 9.9%, hydronephrosis 4.4%, polycystic kidney was 0.0%, renal hypoplasia was 2.2%, renal tumor was 0.0% and Meckel-Gruber syndrome 0.0%. CONCLUSION: The main risk factor associated with recurrent urinary infection in girls aged 6-12 years are urinary malformations